E-Marketing Mixes and Their Influence on Business Growth: Evidence from SME Leaders in Erbil, Kurdistan Region - Kareem, Jamal Ahmed Hama; Mahmood, Ronyaz Hayyas; Mohammed, Hazhar Omer; Abdullah, Nabaz Nawzad (Transpublika Publisher, 2025)
The advent of e-marketing has transformed the business landscape, offering small and medium enterprises (SMEs) a powerful tool for growth, particularly in emerging economies like the Kurdistan Region of Iraq. In Erbil city, SMEs face the dual challenge of leveraging digital tools for competitiveness while operating within a unique socio-economic context. This study aims to investigate the impact of electronic marketing on business growth in small and medium enterprises (SMEs) in Erbil city. To achieve this end, the researchers utilize analytical descriptive approaches. Using a quantitative case study methodology, data were collected through a pre-tested, structured questionnaire distributed to 85 e-marketing group leaders in Erbil City. A total of 79 valid responses were obtained for statistical analysis. The study yielded multiple conclusions, indicating a substantial and positive correlation between the adoption of e-marketing mixes and business growth, illustrating that the proficient utilization of digital marketing tools enhances revenue growth, market expansion, and customer engagement. The research presented a set of recommendations; the most important thing is that small and medium-sized firms ought to aggressively employ social media marketing to promote brand awareness and foster client involvement, while collaborating with local influencers can bolster brand recognition and broaden reach in the Kurdistan market.